Effects of a 4-week weightlifting or plyometric training mesocycle on physical performance in highly trained adolescent basketball players - Ricart-Luna, B.; Domínguez-Navarro, F.; Gene-Morales, J.; Colado, J. C.; Juesas, Á.; Portes, R.; Chulvi-Medrano, I. (Journal of Sports Sciences, 2025)
This study examined the effects of weightlifting (WTG) and plyometric (PTG) training on ankle mobility, strength, power, and running performance in highly trained adolescent basketball players. Participants (male, n = 23; female, n = 35) were randomly assigned to WTG or PTG, training three times weekly for four weeks. Assessments included ankle dorsiflexion, hip strength (ABD-ADD ratio and asymmetry), handgrip strength, lower limb power (Counter Movement Jump -CMJ- and Broad Jump), and running performance. Both interventions significantly improved ankle dorsiflexion (left: p < .001, d = 1.10; right: p < .001, d = 1.50) and hip strength (left adduction: p = .001, d = 0.93; right abduction: F[1,54] = 6.65, p = .013, d = 0.71). The WTG improved right handgrip strength (m.d. 1.76 kg, p = .028, d = 0.23) and CMJ (m.d. 1.81 cm, p = .004, d = 0.30). Both groups improved Broad Jump performance (WTG: m.d. 0.13 m, p = .002, d = 0.46; PTG: m.d. 0.13 m, p = .007, d = 0.47). The PTG showed significant improvement in the Compass Drill (p = .003, d = 0.42). Both interventions have the potential to enhance physical performance, with no clear superiority for one type of training over the other.